Contesting war memories: Parties and voters in contemporary Southeast Europe. (November 2022) - Glaurdić, Josip; Lesschaeve, Christophe; Mochtak, Michal
Over the past four decades, there has been a proliferation of interest in the causes, consequences, and dynamics of contestation over collective memories across a variety of fields. Unfortunately, collective memories—particularly those of traumatic experiences of violence such as wars and revolutions—have been largely absent from party politics research. Using data collected in an expert survey on the policy positions and ideological orientations of all relevant political parties, as well as an extensive survey of more than ten thousand voters in the six post-conflict countries of Southeast Europe, we demonstrate that collective memories of war are not only subjects of historiographical contestation but are also significant sources of ideological and policy differentiation among political parties, as well as one of the strongest determinants of voter choice. Our analysis shows that collective memories are politically contested and that party politics research would benefit from taking them seriously.